Potential role of uric acid to activate NLRP3 inflammasome triggering endothelial dysfunction in preeclampsia - Nunes, Priscila Rezeck [UNESP]; Romao-Veiga, Mariana [UNESP]; Peracoli, Maria Terezinha Serrao [UNESP]; Peracoli, Jose Carlos [UNESP]; Sandrim, Valeria Cristina [UNESP] (Elsevier, 2022)
Preeclampsia (PE) is a pregnancy-related disorder associated with increasing maternal death rates and affecting 2–8% of pregnant women worldwide. Arterial hypertension and proteinuria, followed by other maternal dysfunctions are classic clinical parameters to identify this disease. Furthermore, hyperuricemia is strictly related to PE, and high plasmatic levels of uric acid have been associated with disease severity. The inflammation in the endothelium caused by danger signals, such as uric acid crystals, is persistent and stimulates the release of inflammatory cytokines, and activates the NLRP3 inflammasome. The mechanisms underlying endothelial dysfunction induced by the metabolism of uric acid, and consequently increased levels of inflammation and oxidative stress in women with PE could be ameliorated with interventions related to inhibition of the NLRP3 activation MSU-mediated and may improve the prognostics of this disease.
Keywords: Endothelial dysfunction; Hyperuricemia; Inflammation; NLRP3; Oxidative stress; Preeclampsia; Uric acid